Variability and character association studies for yield and yield contributing characters in cucumber (Cucumis sativus) under low hills of Himachal Pradesh - RANI, RIYA; DOGRA, B S; SINGH, SHIV PRATAP; KUMARI, SANTOSH; SHARMA, PALLAVI (The Indian Journal of Agricultural Sciences, 2023)
Cucumber is an important member of family Cucurbitaceae having potential applications across many sectors. Twenty genotypes were evaluated at the Department of Vegetable Science, College of Horticulture and Forestry (Dr Yashwant Singh Parmar University of Horticulture and Forestry), Neri, Hamirpur, Himachal Pradesh during June– September 2021 for studying variability in morphology, yield and its contributing traits. In studying genetic parameters, PDI of downy mildew, number of fruits/plant, total yield per plot and PDI of powdery mildew, traits showed high estimates of PCV and GCV, indicating the considerable amount of variation was present in germplasm. Most of the traits under study showed high heritability with high to moderate genetic advance as a per cent of mean, which showed the influence of additive gene action for controlling traits. Thus, selection is effective for improvement in these cucumber genotypes. Correlation association and path analysis showed fruit length, fruit breadth, internodal length, number of fruits per plant, harvest duration and ascorbic acid. These traits were considered during the selection of superior genotypes among the twenty genotypes. Thus, in this study, LC-C-4-21 and LC-C-14-21 were higher yielders and can be used for further breeding programmes.